Passive Leadership and Cyberloafing: The Dual Mediating Roles of Negative Emotions and Interactional Justice among Indonesian Millennial Workers - Febriana, Silvia Kristanti Tri; Al Banna, M. Biya Rasyid (Universitas Ahmad Dahlan, 2025)
Millennials, known for being “always connected,” use the internet extensively for information but are also at risk of cyberloafing. This study, based on the transactional theory of stress and coping (Lazarus & Folkman, 1987), examined the impact of passive leadership on cyberloafing through the mediating roles of interactional justice and negative emotions among Indonesian millennial workers. This cross-sectional research employed purposive sampling to collect data from 634 workers aged 26 to 42 years. Measurements included the Cyberloafing Scale, the Justice Scale, the Job-Related Affective Well-Being Scale, and the Multifactor Leadership Scale. The findings revealed that negative emotions significantly and partially mediated the effect of passive leadership on cyberloafing (t = 9.014, p = 0.000). However, interactional justice did not significantly mediate this relationship (t = 0.021, p = 0.983), although passive leadership influenced perceptions of interactional justice. These findings suggest implications for leadership development and workplace well-being initiatives. Organizations may benefit from fostering proactive leadership styles, enhancing transparent communication, and creating psychologically supportive environments. Moreover, interventions aimed at improving employees’ emotional regulation and coping strategies could be valuable in mitigating the negative effects of passive leadership on work behavior.